2019
DOI: 10.1021/acssuschemeng.9b00624
|View full text |Cite
|
Sign up to set email alerts
|

Proline-Mediated Knoevenagel–Doebner Condensation in Ethanol: A Sustainable Access to p-Hydroxycinnamic Acids

Abstract: Naturally occurring p-hydroxycinnamic acids were obtained using an amine-and toxic solvent-free Knoevenageltype pathway. This method uses not only non-toxic reagents (i.e., L-proline and magnesium oxide as catalyst) and ethanol as green solvent, all reagents and solvent being renewable and accessible at low price. By combinaing a Design of Experiment and a One Variobale At a Time optimization (OVAT), the different reaction parameters optimized in order to favor sinapic acid synthesis over that of the two other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…It is important to note that, for this study, ferulic diacid production from vanillin and malonic acid was selected as the model reaction. As reported in a previous work by Peyrot et al, phydroxycinnamic acids can be obtained through Knoevenagel-Doebner condensation between phydroxybenzaldehydes and malonic acid in ethanol using proline as catalyst [27]. It was observed that the mechanism of the p-hydroxycinnamic diacid formation strongly depends on the reaction conditions as depicted in Figure 2.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…It is important to note that, for this study, ferulic diacid production from vanillin and malonic acid was selected as the model reaction. As reported in a previous work by Peyrot et al, phydroxycinnamic acids can be obtained through Knoevenagel-Doebner condensation between phydroxybenzaldehydes and malonic acid in ethanol using proline as catalyst [27]. It was observed that the mechanism of the p-hydroxycinnamic diacid formation strongly depends on the reaction conditions as depicted in Figure 2.…”
Section: Resultssupporting
confidence: 53%
“…It was observed that the mechanism of the p-hydroxycinnamic diacid formation strongly depends on the reaction conditions as depicted in Figure 2. In their study, the formation of ferulic diacid in 68% yield was observed using the following conditions: 1 equivalent (eq) of vanillin in ethanol (0.5 M), 3 eq of malonic acid, and 1.1 eq of proline, 16 h at 40 °C ( Figure 3) [27]. This result served as foundation for the optimization of the phydroxycinnamic diacid synthesis.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations